Pengaruh Penerapan Penurunan Nilai Aset Tetap Menurut Psak 48 Terhadap Laporan Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Pertiwi, Ayu Rahmaniar; Sutarti, Sutarti; Hasibuan, David H M (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
Fixed assets are tangible assets owned and used in production or providing goods and/or services, for rent to other parties or for administrative purposes and are forecasted to be made of service for more than a period of time and occasionally decreased in value due to the unrecoverable amount of the expected return compared to its booked value. Fixed assets decrease happens when the carrying amount/book value is higher than the expected recoverable amount. Recoverable amount is the higher value produced by the fair value when subtracted by selling cost and value in used. This research is designated to investigate the application of accountancy on the decreasing values of fixed assets on financial reports of manufacturing companies, whether they are already in accordance with the PSAK 48 (2014 revision); and to determine the effect of impairment of fixed asset value to the financial statements of manufacturing companies. This study uses descriptive-qualitative analysis and purposive sampling in the sample selection in which suitable for the applied criteria, and obtained 5 sample of 143 manufacturing companies. The data used are of secondary one obtained by downloading from the Indonesian Stock Exchange site. The study shows that most companies have complied to the PSAK 48 (2014 revision). Where of the 5 sample companies, 1 of them found to have released an inappropriate decreased fixed asset value in their notes of financial statements of 2015 and 2014. Based on the analysis, this indicates that fixed asset decrease has a negative influence and it is proven by fixed asset value presented in the financial statement and disclosed in the notes that its booked value is higher than the expected return, and that there is fixed assets value decrease acquired and recognized in the comprehensive income statements.